The dynamic development of the legal status of crimes against property in the XXI century (International relations and international law Journal, 2016)
The main purpose of this article is to introduce the crime against property as well as their category. Every independent state has the power to determine the number of benefits and begin, commit against the property of a citizen and as individuals. Thus, we wanted to show that at the time these crimes are developing at a high speed, and they affect the economy of the state. Kazakhstan and the state that international relations Immersed mutual exchange experience in combating this crime. Crimes against property are different in nature to the base. A group of crimes against property and other utilitarian purpose of extortion, fraud or abuse of trust, criminal damage to property by knowingly purchase or sale of property found in violation of the rights of intellectual property, as well as the theft of a car or other vehicle, improper, illegal ownership. Ax to grind are crimes against property are made for the purpose of : violations of property rights in relation to the ground, someone else ‘s intentional destruction or damage of property.
Keywords: against property; profit; property; criminology; theft against property; looting; crime